(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Without a doubt, our society underwent a radical change with the health emergency, where technology plays an important role in establishing, through its use, specialization tools for the identification of high-impact scenarios for the implementation of technology for the Education sector. These scenarios involve technological projects such as: e-Mexico and Connected Mexico, Connected Cities, which strengthen the objectives and strategies to improve the control and access to information in various public spaces for the use of the Internet. Likewise, as an objective of this study, the strategy for determining the sites proposed in the last federal program of importance for the educational sector, which identifies 6,763 sites, will be analyzed. Similarly, the main strategies and technological vision of this project and its link with universities for technological growth in the midst of this health crisis will be explained.